Spectrophotometric Determination of Chlorpromazine -HCI by Ion -Pair Complex Formation with Acid Dyes
A simple, rapid, accurate and sensitive spectrophotometric method is proposed for the detennination of chlorprQm<tZine -HCl in pwe form and in pharmaceutical formulation. This method is based on the formation. of ion assodation complexes of dmg with either thymol blue or bromophenol blue in an acidic buffer at pH values 4.17 and 3.68, respectively. The ion-pair complexes formed exhibit absorption maxima at 41 Onm for both thymol blue and bromophenol blue. These complexesÂ· are quantitatively extracted with chloroform. The calibration graphs are tmear and obeyed Bee ’s law in a cort.ce n:at_ion range of 50-450fg!ml and H: